The Sensitivity Level of the Coastal Areas in Bulukumba Regency to Waste Pollution - Adinuha, Dinda Afifah; Agus, Syamsul Bahri; Zamani, Neviaty Putri (Journal of Applied Geospatial Information, 2023)
The presence of waste in coastal environments can lead to increased coastal damage and burden. Most of the population's activities in Bulukumba Regency are concentrated in coastal areas, thus making this region susceptible to significant pressure from waste pollution. This research aims to determine the level of coastal area sensitivity in Bulukumba towards waste pollution. The study was conducted from October to December 2022. The research location is the coastal area of Bulukumba Regency, which includes seven subdistricts: Gantarang, Ujung Bulu, Ujung Loe, Bonto Bahari, Bontotiro, Herlang, and Kajang. Primary data were obtained through interviews and direct observations at the research locations, while secondary data were collected through literature studies and relevant institutions in Bulukumba. The results of parameter weighting using the expert judgment method indicate that five important parameters are used to assess the sensitivity of the coastal environment to waste pollution. These parameters consist of current velocity (20.27%), distance of the ecosystem from the harbor (18.92%), distance of the ecosystem from settlements (18.92%), distance of the ecosystem from rivers (17.57%), and the presence of waste on the coast (17.57%). The distribution of coastal environmental sensitivity levels to waste pollution shows that the eastern coastal areas are more sensitive to waste pollution than the southern coastal areas. The current velocity is the most significant parameter influencing the coastal environment's sensitivity to waste pollution and holds the highest weight and score across all research areas.